Platelet, fibrin and leukocyte-rich clot (PFLRC) clot for diabetic foot ulcer healing - Cases report - Pedraza-La Barrera, Joan; Landeo-Solis, Mareth Fiorella; Rodriguez-Alonso, Dante Horacio; Rosas-Garay, Diego Armando; Rosas-Oliveros, Jorge; Becerra-Gutiérrez, Lizzie Karen; Tello-Vera, Stalin (Acta Biomedica Atenei Parmensis, 2026)
Diabetic foot ulcers (DFUs) are common and serious complications of diabetes, associated with a high risk of infection, amputation, and reduced quality of life. Conventional therapies, such as biocompatible dressings, have limited regenerative capacity and are costly, especially in developing countries. Orthobiological agents such as platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) in gel form have shown potential for healing, but their preparation is complex. The study presents the efficacy of a new regenerative therapy protocol for diabetic foot using a low-cost, easily obtainable autologous three-dimensional orthobiological agent or clot rich in red blood cells, fibrin, platelets, and leukocytes (RF-LR). Three clinical cases of patients with DPF treated with four sessions of RF-LR are reported. Complete closure of the lesions was observed, with no recurrence for at least three months. Preliminary results suggest that RF-LR could be a safe, effective, and affordable alternative to conventional treatments and more complex orthobiological therapies. However, randomised controlled clinical trials are needed to validate its efficacy and establish its application in standardised therapeutic protocols.